x^3-49x=?                                                                                                      0,16y-3y=?                                                                                                        81x^2-9=0                                                                                                     16-4y^2=0

  • x^3-49x=x(x^2-49)=x(x-7)(x+7)

     16-4y^2=0    4-y^2=0  (2-y)(2+y)=0  y=2    y=-2

     81x^2-9=0    9x^2-1=0 (3x-1)(3x+1)=0   x=1/3   x=-1/3

      0,16y-3y=-2.84y